Diagnostic molecular biology - Shen, Chang-Hui (Cambridge, Massachusetts Academic Press, 2023)
"Diagnostic Molecular Biology, Second Edition provides an up-to-date comprehensive overview of the latest advances in molecular diagnostics and the fundamental molecular aspects in this area. The book delves into the essential principles behind the transmission and expression of genetic information, including nucleic acids, proteins, and chromosomes, specifically their genome structure, life cycle, and evolution. The latest methods and instrumentation in the field are examined with detailed procedures and explanations provided for each technique. A range of techniques are also investigated, such as those used in sequencing analysis, genome and transcriptome analysis, and nucleic acid amplitification techniques. This book covers the collection, isolation, and purification of DNA, RNA, and protein from different sources. Additionally, discussion on the applications of next-generation sequencing (NGS) and the role of NGS in the future of precision medicine is included. The book also examines the use of molecular diagnostics for chromosomal disorders, inherited diseases, and infectious diseases. Moreover, this new edition features recent advances in the detection of respiratory virus infections in humans, including that of SARS-CoV2. Diagnostic Molecular Biology, Second Edition, is an ideal reference for researchers, lab technicians, and students in medical laboratory science, molecular biology, microbiology, virology, and related fields."
Includes bibliographical references and index.
Keywords: Medical laboratory technology; Molecular diagnosis; Genomics -- Diagnostic use; Molecular biology -- Diagnostic use; Nucleic acids -- Analysis